Estimating the defense spending vote. (September 2015) - Williams, Laron K.
Abstract: Systematic evidence linking defense spending preferences to electoral choice has evaded scholars. This is surprising, given the relative importance of defense spending in terms of the overall budget, as well as the popular conception that increases in defense spending must be offset by decreases in social spending. I develop a theory that identifies the conditions where, when, and for whom defense spending preferences influence vote choice. I then introduce a new method that isolates the defense spending vote with a series of survey-specific models that account for factors unique to the particular situation in that country. I find that—contrary to conventional wisdom—defense spending preferences consistently influence vote choice. This presents an opportunity for right-wing parties and those that emphasize military buildups to attract votes, especially during times of heightened international tensions. These results highlight a strong connection between voters' preferences and electoral support in terms of national security issues, and speak to a number of important literatures including the constraining effects of public opinion on foreign policy and democratic representation.